The underestimated and under rated role of Physiotherapists during COVID-19 in Pakistan - Hafsa Imtiaz Khokar (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2020)
Physiotherapists are healthcare professionals having direct contact with patients suffering from chronic disorders including COVID-19 [1]. Physiotherapists are also among the practitioners taking responsibility for the wellbeing of the COVID-19 and other infectious diseases management and outcomes thus sharing handsome amount of workload with healthcare systems [2].